Renal Artery Caliber In Abdominal CT Scan With IV Contrast Based on Age and Gender - Tarigan, Novrida Pratiwi; Daulay, Elvita Rahmi; Nasution, Syafrizal (CoinReads Media Prima, 2022)
Introduction: CT scan provides several three-dimensional images when reconstructed, high speed, accurate, less invasive, and relatively low cost. The size of renal arteries varies based on influencing factors such as age, gender, and location. Several studies reported variations in the dimensions of the renal arteries based on sex, age, and variations of the arteries. The purpose of research objectives is to analyze factors affecting the caliber of the renal artery in patients with abdominal CT Scan with intravenous contrast procedure. Method: A case-control study in patients with abdominal CT Scan with intravenous contrast procedure. Data was secondary data obtained by medical records of patients who have undergone a CT scan of the Abdomen with intravenous contrast. Results: The caliber of the right renal artery in subjects ≤40 years (5.19±0.53 mm) was greater than those> 40 years (4.58±0.66 mm). Statistically, based on the Independent T-test, found that there was a significant difference in the mean caliber of the right renal artery (p <0.01) and the left renal artery (p=0.01). The mean of the caliber of the right and left renal arteries in male subjects (5.05±0.69 mm) was greater than women (4.7±0.60 mm). The results of the Independent T-test showed that there was a difference in male subjects than women with a p-value of the right renal artery caliber (p=0.04) and left (p=0.02). Conclusion: There was a difference in the mean caliber of the renal arteries by the CT scan of the abdomen with intravenous contrast based on age and gender.